(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Cytokines are responsible for the modulation of immunological and inflammatory processes and play a significant role in the pathogenesis of acute coronary syndrome patients (ACS). Objective:This study aims to investigate the serum levels of IL-1? and IL-6 in ACS patients. Methods: The study covered 140 subjects. It comprised a total of 101 patients with ACS patients [62 with acute myocardial infarction (AMI) and 39 with unstable angina (UA)], compared with 39 healthy individuals with no history of cardiac disease. Serum IL-1? and IL-6 analysis was performed by ELISA. Results:The present results revealed that there were significant elevation in mean serum levels of IL-1? and IL-6 in patients with ACS ( AMI and UA) as compared to healthy control (P